From Crisis to Calling: Ignatian Leadership as Transformative Pedagogy in Contemporary Higher Education - Núñez-Lagos, José María Villanueva (Journal of Jesuit studies, 2025)
Contemporary university students face a profound crisis of meaning, marked by technological acceleration and existential fragmentation. This article presents the Ignatian Leadership course as a required subject within the university curriculum, conceived as an experiential and countercultural response rooted in the Jesuit educational tradition. Through a qualitative and hermeneutic approach, it articulates a path of personal and communal transformation based on seven interrelated attributes: self-knowledge, inner freedom, discernment, magis, meaning, love, and transcendence. The proposals analyzed offer an anthropology of vocation, an experiential spirituality, and an integrative pedagogy. This research draws upon academic literature, pedagogical experience, and both qualitative and quantitative data from programs implemented at Universidad Pontificia Comillas, Creighton University, Ateneo de Manila University, and the Programa de Liderazgo Ignaciano Universitario Latinoamericano (PLIUL). The study highlights the transformative power of this bold initiative to renew the mission of the university and accompany young people in their search for fullness.